Electrospun nanofibers and their application as sensors for healthcare - Zhao, Yi-Sa; Huang, Jie; Yang, Xingjian; Wang, Weqiang; Yu, Deng-Guang; He, Hua; Liu, Ping; Du, Kewei (Frontiers in Bioengineering and Biotechnology, 2025)
Electrospinning is a type of electrohydrodynamics that utilizes high-voltage electrostatic force to stretch a polymer solution into nanofibers under the influence of an electric field, with most of the fibers falling onto a collector. This technology is favored by researchers across various fields due to its simple and inexpensive device for producing nanofibers in a straightforward manner. Nanofibers prepared through electrospinning have a high specific surface area and high porosity. Electrospinning technology shows extensive potential, especially within biomedical sensors. This article provides a systematic overview of the factors influencing electrospinning, the parameters of the electrospinning process, the types of electrospun nanofibers, and the applications of electrospinning technology in the field of sensors, including wearable sensors, pressure sensors, and glucose sensors. The paper summarizes the research progress in this field and points out the direction of development for electrospinning technology, as well as the future challenges.